2006
DOI: 10.1002/bsl.699
|View full text |Cite
|
Sign up to set email alerts
|

Opinion formation in evaluating the adjudicative competence and restorability of criminal defendants: a review of 8,000 evaluations

Abstract: Evaluations of competence to stand trial (CST) are the most common type of criminal forensic evaluation conducted, and courts tend to defer to clinician opinions regarding a defendant's competence. Thus, it is important to study the ways in which clinicians arrive at opinions regarding adjudicative competence and the data they consider in forming their opinions. We reviewed 8,416 evaluations conducted by forensic evaluators in Virginia over a 12 year period, and examined (a) the clinical, demographic, and crim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
4
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(114 citation statements)
references
References 29 publications
6
103
4
1
Order By: Relevance
“…This was an unexpected result and the opposite of that found in a recent U.S. study (Warren et al, 2006). It may be that psychologists in the present study were involved in cases primarily concerning cognitive abilities including intellectual disability that may be more contentious.…”
Section: Discussioncontrasting
confidence: 78%
“…This was an unexpected result and the opposite of that found in a recent U.S. study (Warren et al, 2006). It may be that psychologists in the present study were involved in cases primarily concerning cognitive abilities including intellectual disability that may be more contentious.…”
Section: Discussioncontrasting
confidence: 78%
“…Given that the Warren et al, 2006 report suggests that psychologists are far more involved in reporting on mental fitness in the United States than this study found occurs in South Australia, it is worth further consideration of the differences which may lead to the apparent underutilization of psychologists in the process in South Australia. To be registered as a psychologist in the United States requires the practitioner to hold a doctorallevel qualification À something that is not required in Australia.…”
Section: Psychology and Psychiatry In Fitness To Stand Trial Hearingsmentioning
confidence: 82%
“…The first two cases (R v. Stevens; R v. Kola) bear on the issue of the use of psychological tests, the next case (R v. Millar No 2) illustrates judgments which included both complimentary and critical comment regarding the evidence of expert witnesses and the last case (R v. Bober) shows the care given to the fitness to plead concept by the court. The use of neuropsychological and other fitness tests has long been a controversial area with regard to fitness to stand trial in Australia and overseas (Heilbrun, 1992) although evidence suggests that forensic assessments are made largely on the basis of clinical skills without support from psychometric tools (Warren et al, 2006;Winick, 1995). Specific tests for mental unfitness for trial are not generally used in South Australia due to the lack of availability of appropriate Australian standardized instruments.…”
Section: Illustrative Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, between 60 and 77% of all defendants found not guilty by reason of insanity are diagnosed with a psychosis, and at least 10% of these individuals have a diagnosis of neurologically based psychosis (Cochrane, Grisso, & Frederick, 2001;Warren et al, 2006). This suggests that, while neuroimaging evidence might currently pose unfair bias in some criminal trials, the evidence is certainly relevant to many cases and should not be excluded wholesale.…”
Section: The Roles Of Neuroimaging Data In the Courtroommentioning
confidence: 92%